Current approach to the diagnosis of sarcopenia in cardiovascular diseases - Han, Xu; Zhang, Gao Sen; Li, Qi Rui; Zhang, Zhen (Frontiers in Nutrition, 2024)
Muscle wasting syndrome, also known as sarcopenia, is an age-related geriatric condition characterized by a gradual loss of muscle mass, strength, and function. Sarcopenia can be classified into primary and secondary types. Primary sarcopenia is primarily associated with aging, while secondary sarcopenia is caused by systemic diseases such as cancer, diabetes, liver cirrhosis, musculoskeletal disorders, and disuse changes. In recent years, increasing evidence suggests that cardiovascular diseases can promote the occurrence of sarcopenia through various pathophysiological mechanisms. Additionally, sarcopenia increases the risk of adverse outcomes in patients with cardiovascular disease such as rehospitalization and mortality. Therefore, screening and diagnosing sarcopenia are particularly important for patients with cardiovascular diseases. This article provides a brief overview of the research progress on diagnostic methods for sarcopenia in patients with cardiovascular diseases. suffering from CVD, and reduced muscle mass independently contributes to the risk of mortality associated with such conditions(11), thereby significantly impacting both the quality of life and prognosis for these patients (12,13). Therefore, in the clinical diagnosis and treatment of CVD patients, accurately assessing and intervening in muscle wasting is becoming increasingly important.